Groundwater from Fractured Granite and Metasedimentary Rocks in the West Coast of Peninsular Malaysia - Sapari, Nasiman (Universiti Putra Malaysia, 2012)
Hard rock formation,s consisting of granite and metasedimentary rocks in Peninsular Malaysia, have been considered to be of poor aquifers. The hydrogeologic map of the Malay Peninsular in 1975 shows the area underlain by hard rock as having poor to moderate potential for groundwater production (<230m3/ well/day). This paper presents a finding of productive hard rock aquifers in the west coast of Peninsular Malaysia. Data from tubewell drillings carried out for industrial water supply were analyzed. It was found that the hard rocks could yield fresh water up to a maximum of 890m3/well/day. The wells were between 50 m and 200 m deep. High discharge rates of groundwater above 300m3/well/day were encountered from wells that penetrate major fracture zones. The hard rocks are generally fractured at various depths. Groundwater in interconnected fractures has a steady flow that sustains production during pumping tests and actual usage of the wells. This phenomenon indicates that the groundwater is being recharged by infiltration of rainwater through the overlying weathered rocks and soils. Tubewells in hardrock of West Coast of Peninsular Malaysia were found to have average discharge rates of 343m3/well/day. However, some of the deep tubewells that are more than 150 m depth, penetrated only weathered granite, are generally non productive (<70m3/well/day). Limited fracture openings and restricted recharge areas are likely to be the reason for the low discharge. Clay particles in fractures were observed to be the factor for the low success rate and poor quality of the water particularly in metasedimentary areas.